Plant ecology of tropical and subtropical karst ecosystems - Geekiyanage, Nalaka; Goodale, Uromi Manage; Cao, Kunfang; Kitajima, Kaoru (Biotropica, 2019)
Substantial areas of tropical forests, including those within nine tropical biodiversity hotspots, contain karst landscapes that have developed on soluble carbonate rocks. Here, we review how the ecology of karst forest trees is influenced by hydrological, edaphic, and topographic factors that exhibit fine spatial heterogeneity. Comparative analysis of drought tolerance traits including wood density contributes to the assessment of whether karst tree species are more drought-tolerant compared to non-karst trees. Although karst ecosystems are generally considered to have low phosphorus availability, foliar nitrogen-to-phosphorus ratios exhibit wide variation across karst regions without a clear difference from non-karst ecosystems. According to the analyses of leaf phenology, stem water storage, and isotopic signatures from xylem sap, water use strategies of karst trees can be classified into five types: (a) soil water dependent, (b) epikarst water dependent (mainly use water stored in fine pores and gaps within the epikarst rock during the dry season), (c) groundwater dependent, (d) fog water dependent, and (e) drought-deciduous (shed leaves during the dry season). Overall, published data suggest that only a subset of karst tree species are exclusively distributed within karst hilltops where water availability is limited. The diverse resource acquisition and utilization strategies of karst plants across edaphic habitats must be considered when developing effective strategies to conserve and restore biodiversity in karst landscapes, which are under increasing anthropogenic pressure.